Strategic Location of Fluid Viscous Dampers in High-rise Reinforced Concrete Buildings for Seismic Resilience: A Comparative Analysis - Tallapragada, Sai Datta Phanindranath; Kokkirala, Venkata Gopala Dhana Rao Balaji; Bantupalli, Ramesh; Ponnada, Markandeya Raju; Kapuganti, Chitti Babu (Journal of Engineering and Technological Sciences, 2025)
High-rise reinforced concrete (RC) buildings are highly vulnerable to seismic forces due to their ‎inherent structural limitations, necessitating effective energy dissipation mechanisms. Conventional ‎damping strategies often fail to adequately control excessive vibrations, leading to potential ‎structural damage. Fluid Viscous Dampers (FVDs) offer a novel approach by significantly ‎improving energy dissipation and reducing seismic responses. However, the optimal configuration, ‎placement, and quantity of FVDs in high-rise buildings remain insufficiently explored, ‎necessitating this study. This research introduces a novel damper placement framework by ‎investigating the strategic positioning of FVDs in a 25-storey RC benchmark building, evaluating ‎‎80 damper configurations using non-linear time history analysis in ETABS. The study compares ‎Strategic Location Formats (SLFs) against Arbitrary Location Formats (ALFs) and Uniformly ‎Distributed Frames (UDFs) to determine the most effective and economical damper placement ‎strategy. Findings reveal that SLFs achieve superior seismic performance while using significantly ‎fewer dampers, demonstrating an innovative and cost-effective approach to structural damping. ‎SLFs achieve up to 45% reduction in displacement, 56% reduction in inter-storey drift, and 54% ‎reduction in base shear, using only 36 dampers, compared to 96 in ALFs and 192 in UDFs. ‎Additionally, SLFs are highly cost-efficient, requiring only 9% of total construction costs, ‎compared to 24% for ALFs and 49% for UDFs. This study establishes a novel, performance-based ‎damper placement framework, offering a scientifically validated methodology for optimizing ‎seismic resilience while maintaining economic feasibility. These findings make SLFs a ‎transformative solution for high-rise RC buildings in earthquake-prone regions.